2010
DOI: 10.1177/1087057109351027
|View full text |Cite|
|
Sign up to set email alerts
|

Gradient, Contact-Free Volume Transfers Minimize Compound Loss in Dose-Response Experiments

Abstract: More accurate dose-response curves can be constructed by eliminating aqueous serial dilution of compounds. Traditional serial dilutions that use aqueous diluents can result in errors in dose-response values of up to 4 orders of magnitude for a significant percentage of a compound library. When DMSO is used as the diluent, the errors are reduced but not eliminated. The authors use acoustic drop ejection (ADE) to transfer different volumes of model library compounds, directly creating a concentration gradient se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…7,8 The most significant improvement in data quality is observed when comparing ADE dosing to performing manual serial dilutions in buffer or assay media. 8,9 When serial dilutions are automated and performed in 100% DMSO and then transferred into an assay plate, errors associated with compound carryover/loss are reduced 10 but potentially not eliminated. 9 In 2004, emerging screening data from AstraZeneca Oncology in Alderley Park (AP) indicated that low data consistency was observed in projects working with compound series with high lipophilicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The most significant improvement in data quality is observed when comparing ADE dosing to performing manual serial dilutions in buffer or assay media. 8,9 When serial dilutions are automated and performed in 100% DMSO and then transferred into an assay plate, errors associated with compound carryover/loss are reduced 10 but potentially not eliminated. 9 In 2004, emerging screening data from AstraZeneca Oncology in Alderley Park (AP) indicated that low data consistency was observed in projects working with compound series with high lipophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 When serial dilutions are automated and performed in 100% DMSO and then transferred into an assay plate, errors associated with compound carryover/loss are reduced 10 but potentially not eliminated. 9 In 2004, emerging screening data from AstraZeneca Oncology in Alderley Park (AP) indicated that low data consistency was observed in projects working with compound series with high lipophilicity. Further investigation led to the identification of a number of liquid handling factors during compound solubilization, storage, and dilutions during the screening workflow, which were exacerbated by increasing lipophilicity of test compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of direct dilution using the HP D300 dispenser versus intermediate dilution and pin tool transfer method are (1) elimination of compound serial dilution step, (2) reduction of compound consumption, (3) reducing consumables such as plates and tips used for compound dilution, and (4) prevention of compound cross contamination due to the contact-free nature of dispensing. Direct dilution requires the ability to accurately dispense picoliter volumes and until now, the only other technology capable of such low volume dispensing is acoustic dispensing 8, 9 While both acoustic and inkjet technologies are capable of direct dilution, the HP D300 dispenser has two advantages over acoustic dispensing technology. The HP D300 dispenser has a small footprint that will easily fit into bio-safety hoods to allow compound dispensing into cell plates under a sterile condition.…”
Section: Discussionmentioning
confidence: 99%
“…This is unsurprising, given the number and variety of potential contributing factors. Even for what might be considered a straightforward assay involving fluorescent measurements of a ligand binding to a protein target, this might include (but is by no means limited to): compound impurities and degradation [14], imprecise compound dispensing [5, 6], unmonitored water absorption by DMSO stocks [4], the effect of DMSO on protein stability [7], intrinsic compound fluorescence [8, 9], compound insolubility [10] or aggregation [9, 1114], variability in protein concentration or quality, pipetting errors, and inherent noise in any fluorescence measurement—not to mention stray lab coat fibers as fluorescent contaminants [15]. Under ideal circumstances, control experiments would be performed to measure the magnitude of these effects, and data quality tests would either reject flawed data or ensure that all contributions to error have been carefully accounted for in producing an assessment of error and confidence for each assayed value.…”
Section: Introductionmentioning
confidence: 99%